The Nexus of Covid-19 and Behavioral Intentions of University Students Towards Online Education - Abbas, Sheer; Yaseen, Muhammad; Ameen, Muhammad; Pervaiz, Bushra; Fatima, Sidra; Hassan, Sadia (Emerging Science Journal, 2024)
The onset of the COVID-19 pandemic has significantly disrupted the traditional pedagogical educational system worldwide. The story of Pakistan is also not different from that of the rest of the world. Pakistan’s higher education institutes were closed for classes due to the outbreak. Some universities started the virtual education system, and it is critically important to assess the behavioral intentions of university students toward online education during the COVID-19 pandemic in Pakistan. This is the first study investigating students' responses to online education during the COVID-19 pandemic. For this purpose, an online survey was conducted to obtain the students' responses from the higher institutions providing online classes during COVID-19. The results were evaluated using multivariate analysis and descriptive statistics. It was observed that there is a significant difference between male and female students concerning the positive consequences of COVID-19 on students. According to the findings, the students' intentions for online education are more concerned with saving time to complete the degree program. Higher education institutions should also provide online educational opportunities to students besides traditional physical modes. Online educational interventions will be helpful for students during unavoidable circumstances like political instabilities, natural disasters, viral disease outbreaks, etc. to complete degrees and diplomas. Doi: 10.28991/ESJ-2024-SIED1-02 Full Text: PDF